The impact of smartphone usage towards secondary school students’ academic performance / Mohamad Nafis Baharu - Baharu, Mohamad Nafis (Faculty of Business Management, 2017)
The purpose of this study is to identify or investigate the relationship between smartphone factors towards academic performance of secondary school students. This study is based on the factors and theory from Kibona, L., & Mgaya, G. (2015) which stated that there are three factors that influencing academic performance of higher learning students which are smartphone poisoning, smartphone addiction and smartphone abuse. This study will analyze the factors that influence academic performance among form 4 students in SMK Seri Serdang. Data were collected through questionnaires obtained from 60 respondents. Data collected have been analyzed by statistical technique such as descriptive analysis, reliability, correlation and regression analysis. The finding showed that smartphone abuse has negative significant relationship with academic performance. This study provide recommendation for future research to consider a tracking study by longitudinal time horizon. The result might be more accurate and reliable. The researcher may compare the result finding and analyze the changes of independent variables that influence the dependent variable. The result of this study can create awareness among teachers, parents, school administrator and also students in order to monitor and control the smartphone usage among students.